Sentidos da dimensão tecnológica e trabalho pedagógico entre a pseudoconcreticidade e o concreto pensado nos bacharelados em administração do IFFAR - Andrighetto, Marcos Jose (2024)
This thesis report originated from Kairós – Study and Research Group on Work, Education and Public Policies and is part of Research Line 2 (LP2), of the Postgraduate Program in Education, at the Federal University of Santa Maria ( PPGE/UFSM). The meanings of the technological dimension and pedagogical work in Bachelor's Degrees in Administration at the Federal Institute Farroupilha (IFFar) were investigated. The starting point was the following hypothesis: education developed in the Professional and Technological Education modality is only Professional Education, without considering, in the pedagogical work, the technological dimension. There is a distance between pseudo-concreteness and thought-out concrete. Based on this assumption, the problematization was elaborated: having as reference the dialectical pair: pseudoconcreticity (educational policies, historicity) and the concrete thought (guidelines for the pedagogical work of teachers and for the educational processes of students) in Professional Education and Technological Science in Brazil and, in particular, in Rio Grande do Sul, what meanings of the technological dimension are evident in the pedagogical work in this modality, within the scope of Bachelor's Degrees in Administration at the Federal Institute Farroupilha? As a general objective, it was established: to investigate meanings of the technological dimension in pedagogical work in Bachelor's degrees in Administration, at the Instituto Federal Farroupilha, having as reference the dialectical pair pseudoconcreticity and the concrete thought. To carry out the study, given its specificity, the Analysis of Sense Movements (AMS) was determined as the theoretical-methodological foundation. This is because it is an elaboration of Kairós, with which researchers have carried out their investigations. It is based on dialectical assumptions, and considers the categories historicity, contradiction and totality. In the production and analysis of previous data, AMS made it possible to identify the meanings of technology in the research on EPT already carried out, as well as in the course guiding documents (Institutional Development Plan and Course Pedagogical Projects) and in official speeches (laws, decrees , opinions, ordinances, etc.). To produce data in the empirical field, the focus group technique was selected. The theoretical contribution chosen to support the study is based on historical materialism, with work and education as central categories of analysis. The study carried out confirmed that the technological dimension does not substantiate the pedagogical work in IFFar's Bachelors in Administration, remaining subsumed mainly by educational technologies. In this sense, pedagogical work is based on practical approaches, insertion in the “market”, moving away from work as an educational principle. Likewise, the documents that institutionalize the Course address technology as a nomenclature of curricular components and inserted in technologies for Education. In these terms, despite considering technology as a dimension of pedagogical work in Professional and Technological Education, its absence was found, according to the analysis of the data produced, in the reality investigated. In view of this, the thesis was defended that pedagogical work in EPT consists of five dimensions: 1) historical-ontological; 2) pedagogical; 3) politics; 4) social and 5) technological. Thus configured, TP at EPT has a practical character capable of providing integral and polytechnic training for students, enabling them to transform into emancipated citizens.